THE NEXUS OF CULTURE AND ECONOMICS: A BIBLIOMETRIC ANALYSIS AND VISUALISATION OF CULTURAL ECONOMY. - John, Joshy; Joseph, Soumya T; H, Divya. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The cultural economy is a multidisciplinary field that explores the intersection of cultural values, practices, and industries with their economic impact, encompassing sectors such as heritage, creative industries, and cultural tourism. This study employs bibliometric analysis to investigate the scholarly landscape of the cultural economy using data sourced from the Scopus database. Advanced bibliometric tools, including Biblioshinyand VOSviewer, were used to analyze trends, authorship, and thematic structures. The annual scientific production reveals a steady growth in the field, with a notable surge in publications since the late 1990s. Key contributors, such as Scott, A.J., and Pratt, A.C., along with prominent sources like Geoforum and Journal of Cultural Economy, are identified as central to the field's development. A three-field plot illustrates the interconnected relationships between authors, publication sources, and countries, highlighting the dominance of the United States, United Kingdom, and Australia in global collaborations. Trend topics, such as sustainability, creative cities, and cultural work, reflect the field’s adaptability to contemporary societal challenges, including globalization and environmental concerns. Thematic mapping categorizes research into motor, basic, niche, and emerging themes, emphasizing areas for further exploration, such as gender and migration. Co-occurrence analysis of author keywords highlights the interdisciplinary nature of the field, while country co-authorship networks reveal opportunities for increasing global collaboration. This study provides a comprehensive overview of cultural economy research, identifying trends, gaps, and future directions for advancing the field.